Pengembangan desapreneur berbasis prinsip zero waste melalui valorisasi limbah jagung di Desa Pationgi - Andi Muhammad Irfan Taufan Asfar; Syarif Nur; Taslim Taslim (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Post-harvest corn residues in rural areas are often underutilized, creating environmental burdens while leaving economic potential untapped. This community service program aimed to strengthen the technical, managerial, and marketing capacities of the Pationgi Village community through a desapreneur model based on corn-waste valorization under the zero-waste principle. Key problems faced by partners included low utilization of corn residues, limited access to appropriate technology, and weak skills in processing and marketing value-added products. The program was implemented from September to November 2025 through socialization, intensive training, tool demonstrations, and structured mentoring for two partner groups: the Madeceng Farmers Group and the Makkiade Youth Organization. Three appropriate technologies were introduced and applied, namely PIPILLER, EXTRAFEED, and PIROLIN. The results showed that shelling capacity increased from 80–120 kg/day to 350–480 kg/day, while kernel damage decreased from 15–20% to <5%, accompanied by a reported 12–15% increase in selling value. Partners were also able to produce 150 kg of fermented feed per production session (monthly output ≥150 kg) and generate 10–15 kg of biochar and 3–5 liters of liquid smoke per ±3-hour pyrolysis cycle. Product diversification by the youth group resulted in 10 boxes of corn-silk tea, 20 corn-husk flower crafts, and 5 village-based handicrafts. Evaluation indicated highly positive responses, with all indicators falling within the “agree–strongly agree” categories, although improvement is still needed in tool-component literacy and product packaging. Overall, the program demonstrates that integrating appropriate technology with participatory mentoring can transform corn waste into value-added products and support sustainable rural economic opportunities